The influence of problem based learning model toward studentsâ activities and learning outcomes on financial management subject for undergraduate program students of accounting education - Hardini, Han Tantri; Widayati, Irin (Dinamika Pendidikan, 2016)
The objective of the research was to know influence of Problem Based Learning model toward studentsâ and achievement on Financial Management subject for undergraduate program students of Accounting Education. It was a quantitative research using true experimental design. The samples of this study were undergraduate program students of Accounting Education in the year of 2014. Students at class A were the control class A and at class B were experimental class. The data were analyzed by t-test to determine the differences of their learning outcomes between the control class and the experimental class. Then, the questionnaires were distributed to gather studentsâ activities information in their studentsâ learning model. The results of the study showed that there was an influence of Problem Based Learning model toward studentsâ activities and learning outcomes on Financial Management subject for undergraduate program students of Accounting Education since tcountâ¥ ttable; it was 6.120â¥1.9904. Studentsâ learning activities with Problem Based Learning model were better than students who were taught with conventional learning model.